Unveiling the enigmatic world of female celebgrams in Bireuen, Aceh: Motivations, impacts, and challenges - Thalal, Muhammad; Salsabila, Raudhatul Ula; Hidayatullah, Putra; Kesuma, Aulia (Universitas Islam Negeri Ar-Raniry, 2023)
This article explores the lifestyle phenomenon of female celebgrams in Bireuen, Aceh, Indonesia. Celebgrams have risen to prominence on Instagram, captivating large audiences and influencing trends across various sectors. The study investigates the motivations driving individuals to become celebgrams, the effects of their increasing influence, and the challenges encountered in their digital journeys. Using qualitative research, interviews were conducted with notable female celebgrams from Bireuen, offering valuable insights into their experiences and career paths. The findings reveal that economic factors significantly motivate individuals to embark on this path. Initially, they seek popularity and recognition on the platform, employing creative content, strategic interactions, and hashtags to amass a substantial following. Subsequently, they capitalize on their success, leading to enhanced earning potential. The research highlights both positive and negative consequences of being a female celebgram. On one hand, these women enjoy heightened popularity, vast follower counts, and increased income. On the other hand, they grapple with challenges like loss of privacy, exposure to public scrutiny, and the perpetual need for creativity to maintain their digital identity. The article concludes with recommendations for female celebgrams to preserve a positive image on social media and urges users to develop a critical mindset when consuming content. Furthermore, it encourages future researchers to delve deeper into this phenomenon, enriching our understanding of female celebgrams' influence on Acehnese society and culture.